GOTERA CARD MEDIA: ENHANCING THE STUDENTS' CREATIVITY ON THE TOPIC OF MUTUAL COOPERATION IN THE LOCAL COMMUNITY - Imarda Naina Firga; Deasylina da Ary (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to develop, test the feasibility of, and measure the effectiveness of the GOTERA Card (Mutual Cooperation with Dance Arts) learning media in enhancing the creativity of fifth-grade elementary school students on the topic of cooperation in their local community.Methodology – This study employs a Research and Development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation) and a mixed-methods approach. Data collection included pretests, posttests, expert-validation questionnaires, and teacher- or student-response questionnaires. Feasibility percentages and N-Gain calculations were used for data analysis.Findings – Validation results showed the media was in the very feasible category (content experts: 83%–89%; media expert: 93%). Practicality was rated very practical (teacher: 93.84%; students: 91.76%). Effectiveness results showed N-Gain values of 0.8324 (high category) for the small group and 0.6134 (moderate category) for the large group. The use of this medium has the potential to increase student engagement in learning, foster creativity, and help students understand the value of cooperation through concrete, meaningful learning experiences.Contribution – This research contributes an innovative integrated learning media that combines Pancasila Education content with dance arts activities in the form of concrete interactive cards. The novelty of this study lies in integrating narrative, visual, and kinesthetic approaches into a single learning medium, enabling students to actively engage in meaningful learning experiences while fostering creativity, collaboration, and a deeper understanding of the values of cooperation in Pancasila Education learning.